Electrochemical evaluation of the corrosion behaviour for structural steel SAE 1005 exposed to two different atmospheres (urban and industrial) and comparison with atmospheric corrosion gravimetric measurements. (February 2016) - Salas, Y; Guerrero, L; Castiblanco, H; Torres, C; Palacios, A
Abstract: The Atmospheric corrosion is a phenomenon we see every day in our environment that arises due to environmental pollution we generate, there is currently very little information on atmospheric corrosion in the department of Boyacá and in general, in Colombia. The aim of this paper is to analyse which of these two environments is more aggressive and wherein the steel corrodes faster. To analyse these phenomenon specimens made in steel SAE 105 exposed for five months to the atmosphere in the municipalities of Tunja and Nobsa (an urban atmosphere and other industrial atmosphere) were installed, a control was carried to verify the amount of time that will be exposed each of these samples to the atmosphere, of Thus it may determine the lifetime of a structural steel. For the analysis of these samples electrochemical tests were carried out to calculate the rate of corrosion and resistance to polarization, also the gravimetric method be conducted to compare what was the amount of mass lost during the time of exposure to each of the samples.